(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To study the feasibility of approaches in addressing the mastoid segment of facial nerve through transcanal route exclusively under endoscopic guidance and to verify the usefulness of the pyramidal eminence as a landmark. Study design: The prospective experimental study Setting: “Transcanal endoscopic temporal bone dissection lab” situated in the Surgiscope hospital, Chittagong, Bangladesh. Materials: 4 (Four) cadaveric temporal bones. Interventions: Two pure transcanal endoscopic approaches were applied to excavate the mastoid segment of facial nerve. In anterior-medial approach, the dissection was progressed from medial to the lateral direction through the retrotympanum focusing the anterior-medial side of the mastoid segment of facial nerve. Whereas in anterior-lateral approach, the dissection was progressed from lateral to the medial direction through the posterior canal wall focusing the anterior-lateral side of the mastoid segment of facial nerve. In both approaches, the pyramidal eminence was considered as an anatomical landmark to navigate the dissection for the excavation of the mastoid segment of facial nerve. Main outcome measures: The efficacy of each approach in respect of the complete excavation of the mastoid segment of facial nerve and the worthiness of the pyramidal eminence as the landmark for navigating the dissection. Results: In both transcanal endoscopic approaches, the entire mastoid segment of facial nerve could be exposed successfully. But in anterior-medial approach, the chorda tympani nerve was needed to be sacrificed. The search of the mastoid segment of facial nerve with the guidance of the pyramidal eminence was observed as effective and safe. Conclusion: The entire mastoid segment of facial nerve could be successfully addressed through transcanal route under pure endoscopic guidance. The pyramidal eminence has appeared as an important landmark for such endeavor. Bangladesh J Otorhinolaryngol; October 2019; 25(2): 108-115